Group B streptococcal meningitis presenting as stroke in a nondebilitated man. - Klassen, H. (Yale Journal of Biology and Medicine, 1995)
An unusual case of group B streptococcal meningitis in an adult is described. The evidence presented suggests that early vascular involvement during the meningitic process resulted in cerebral infarction, thereby explaining the patient's sudden deterioration and atypical presentation.